2002
DOI: 10.1046/j.1469-8137.2002.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Uranium uptake and translocation by the arbuscular mycorrhizal fungus, Glomus intraradices, under root‐organ culture conditions

Abstract: Summary• Uranium (U) uptake and translocation by the arbuscular mycorrhizal (AM) fungus Glomus intraradices were studied under root-organ culture conditions with Agrobacterium rhizogenes -transformed carrot ( Daucus carota ) roots as host.• Two-compartment Petri plates were used to spatially separate a root compartment (RC) and a hyphal compartment (HC); root growth was restricted to the RC while extraradical hyphae grew in both RC and HC. The HC was labelled with 0.1 µM 233 U at different pH conditions. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 31 publications
6
73
0
Order By: Relevance
“…Despite this, it has been suggested that AM fungi may eliminate the bioavailability of otherwise toxic contaminants and consequently buffer the soil for plants and other microorganisms (Joner et al 2000). By contrast, Davies et al (2001Davies et al ( , 2002 and Rufyikiri et al (2002Rufyikiri et al ( , 2003 showed, respectively, colonization by G. intraradices enhanced uptake and accumulation of chromium in sunflower and of uranium in cultivated in vitro carrot roots by G. intraradices. Although AM fungi may enhance heavy metal phytoextraction for some plant species, our findings agree with the hypothesis of metal-binding AM fungal capacity as suggested by others (Chen et al 2001, Joner et al 2000, Li & Christie 2000.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Despite this, it has been suggested that AM fungi may eliminate the bioavailability of otherwise toxic contaminants and consequently buffer the soil for plants and other microorganisms (Joner et al 2000). By contrast, Davies et al (2001Davies et al ( , 2002 and Rufyikiri et al (2002Rufyikiri et al ( , 2003 showed, respectively, colonization by G. intraradices enhanced uptake and accumulation of chromium in sunflower and of uranium in cultivated in vitro carrot roots by G. intraradices. Although AM fungi may enhance heavy metal phytoextraction for some plant species, our findings agree with the hypothesis of metal-binding AM fungal capacity as suggested by others (Chen et al 2001, Joner et al 2000, Li & Christie 2000.…”
Section: Discussionmentioning
confidence: 79%
“…Recent phytoremediation studies that incorporated the AM-variable have had mixed findings. Some studies have shown that AM colonization increases the uptake and accumulation of heavy metals in host plants (Davies et al 2001(Davies et al , 2002Hovsepyan & Greipsson 2004;Rufyikiri et al 2002Rufyikiri et al , 6 2003, while others suggested that AM fungi exude enzymes that participate in the immobilization process of soil contaminants, in which case accumulation in plants is reduced (Joner et al 2000, Weissenhorn et al 1993). …”
Section: Introductionmentioning
confidence: 99%
“…At harvest, spore number in RC and HC was assessed by using 1-cm grids marked on the bottom of each petri plate [26]. The roots in RC were collected from the medium by solubilizing the solidified M media with 10 vols of citrate buffer (pH 6.0), and then washed carefully with Milli-Q water and weighed.…”
Section: Assessment Of Variablesmentioning
confidence: 99%
“…The first study on the role of an AM fungus on plant U acquisition was performed by Rufyikiri et al (2002). These authors investigated whether the extraradical mycelium of Glomus intraradices (MUCL 41833) could take up U and translocate it towards its host.…”
Section: Effect Of Phmentioning
confidence: 99%
“…the hyphal compartment, HC) (Rufyikiri et al, 2005). This compartmented in vitro system was preferred by Rufyikiri et al (2002) over bi-compartmented pot systems containing soil because pH of the medium where the extraradical mycelium was developing could be precisely controlled. Indeed, it is known that the pH can play a prevalent role on the process of U uptake because of its effects on the extracellular charges of fungal mycelium (Zhou, 1999;Gadd and White, 1990) and on dominant U species available to the fungal mycelium (Suzuki and Banfield, 1999;Grenthe et al, 1992).…”
Section: Effect Of Phmentioning
confidence: 99%